2008
DOI: 10.1111/j.1365-2230.2008.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve blocks provide effective pain relief during topical photodynamic therapy for extensive facial actinic keratoses

Abstract: Nerve blocks provide efficient pain relief during PDT when treating patients with field cancerization of the forehead. Nerve blocks were not found to affect the clinical outcome of PDT, and were generally well tolerated by the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…When field cancerization on the face and scalp is treated with PDT, all patients are offered NB in advance at our clinic. This is due to previous studies at our clinic that have shown that NB are able to provide adequate pain relief (12,13). It was of special interest for us to acquire more knowledge ofthe patients' different experiences in order to obtain new information on the problems of pain and an opportunity to further develop the use of NB as pain relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When field cancerization on the face and scalp is treated with PDT, all patients are offered NB in advance at our clinic. This is due to previous studies at our clinic that have shown that NB are able to provide adequate pain relief (12,13). It was of special interest for us to acquire more knowledge ofthe patients' different experiences in order to obtain new information on the problems of pain and an opportunity to further develop the use of NB as pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Common methods of reducing the pain are the use of water spray and using a fan to blow cold air; however, these methods are not very effective. An excellent option is to use nerve blocks (NB) (12,13). In order to achieve anaesthesia ofthe forehead and scalp, the supraorbital and supratrochlear nerves are blocked in combination with the greater and lesser occipital nerves (13).…”
mentioning
confidence: 99%
“…Especially in the treatment of large or very sensitive areas nerve blocks represent a valuable option. Studies by Halldin et al 10 and Paoli et al 11 showed that nerve blocks provide impressive pain relief during topical PDT of the forehead, scalp, and face. However, a sufficient reduction in pain reduces the feedback obtained by the patient, which is important to indicate the need for a treatment interruption because of a significant phototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1 for illustration) nerve block and is generally found to be preferred by patients. Facial nerve blocks of cranial nerve V have been shown to improve patient comfort during photodynamic therapy of extensive facial actinic keratosis [6].…”
Section: Which Block To Choose For a Specific Application?mentioning
confidence: 99%